Chemical sensors based on nano-sized lanthanide-grafted periodic mesoporous organosilica hybrid materials. Issue 26 (17th June 2019) - Kaczmarek, Anna M.; Van Der Voort, Pascal
Abstract : Nano-sized PMOs grafted with lanthanides show selective ion sensing for Pb 2+ and Cr 3+ and strong solvatochromism allowing their use as protic and aprotic solvent sensors. Abstract : In this work we introduce the use of nano-sized (50–70 nm) lanthanide-grafted periodic mesoporous organosilicas for both metal ion sensing and solvent sensing. For this study a PMO constructed from the N, N -bis(trimethoxysilylpropyl)-2, 6-pyridine dicarboxamide linker and tetraethyl orthosilicate (at a 5 : 95 ratio) was employed. This material was grafted with Eu 3+, Tb 3+ or a mixture of Eu 3+ –Tb 3+ chloride salts to obtain strongly emitting nano-sized luminescence materials. To further enhance the luminescence properties of the materials two different co-ligands were used – 1, 10-phenanthroline (phen) and 5, 5′-dimethyl-2, 2′-dipyridyl (bpy). The luminescence properties of the developed series of hybrid materials were studied in detail in the solid-state and after dispersing in water. The materials were investigated for their use as ion sensors, with the Eu 3+ and Tb 3+ phen and bpy co-grafted materials showing selective "turn on" fluorescence for Pb 2+ and Cr 3+ ions (at a 10 ppm concentration of the ions). The Eu 3+ –Tb 3+ co-grafted materials showed solvatochromism and could be used as a solvent sensor to distinguish between protic and aprotic solvents.